Choice of root canal irrigants by Serbian dental practitioners - Tošić, Goran; Miladinović, Milan; Kovačević, Milorad; Stojanović, Miodrag (Vojnosanitetski pregled, 2017)
Background/Aim. Root canal treatment is considered to be the one of the most important procedures in endodontic treatment. To irrigate the root canal it is most common to use sodium hypochlorite (NaOCl), chlorhexodine, ethylenediaminetetraacetic acid (EDTA), local anesthetic solution, while the most used in Serbia is hydrogen peroxide (H2O2). The aim of this survey was to reveal the preferred root canal irrigants used by general dental practitioners in Serbia and to determine the influence of the continuing education program, delivered over the 3-year observation period, on work habits of dental practitioners. This was the first comprehensive survey of this nature carried out in Serbia. Methods. The survey was conducted in two instances, a 4-month observation period each, from November 1, 2009 to March 1, 2010 and from November 1, 2012 to March 1, 2013. Internet Web Page Survey was posted on the official web site of the Serbian Association of Private Dentists. In the first survey, 569 completed questionnaires were subjected to analysis. In the next attempt (3 years later), the survey was launched again and 615 completed questionnaires were analyzed using the same criteria. The statistical analysis was carried out with simple descriptive statistics applying the χ2 test, at a significance level of p < 0.05. Results. The first survey included 569 dental practitioners, while 3 years later the number of them was 615. Analyzing the questionnaires revealed the number of 10 to 30 interventins on the root canal montly. The most commonly used irrigant solution was H2O2 in 2009, while in 2012 it was yet H2O2, but also NaOCl, chlorhexodine, and a little less EDTA. Conclusion. This study shows significant changes in the irrigation protocol applied in Serbian dental community. After 3 years of observation, NaOCl became widely accepted as the irrigant of choice, whereas H2O2 lost its popularity.